The Influence of Product Quality and Price on Repurchase Interest Through Consumer Satisfaction at Coffee Shops in Denpasar City - Widnyani, Ni Made; Aristayudha, A.A. Ngurah Bagus; Rettobjaan, Vitalia Fina Carla; Richadinata, Kadek Riyan Putra; Astitiani, Ni Luh Putu Surya (Journal of Economics and Public Health, 2024)
Consumer satisfaction is a measure of the value of a product and service that will affect consumer interest in repurchasing the product or reusing the service. In addition to the quality of the product itself, price is one of the indicators that indirectly affects consumer response to repurchase the goods. This study aims to determine the effect of product quality, price on repurchase interest through consumer satisfaction at coffee shops in Denpasar. Method: This study uses a quantitative method with a differential analytical descriptive approach. The number of samples used was 100 respondents calculated from the number of indicators in the question. The questionnaire used has been tested for validity and reliability. The results of the study were analysed usingalternative structural equation modeling (SEM) method PLS (Partial Least Square) with the SmartPLS 3.0 M3 program. The results of this study indicate that price and consumer satisfaction factors affect consumer repurchase interest, while product quality is not significant to consumer repurchase interest. Mediating consumer satisfaction is proven to only apply to the relationship between price and repurchase interest. Satisfaction indirectly influences consumer repurchase interest in addition to paying attention to product quality and the price of the product itself.